DOI: 10.1016/s1569-3767(00)01010-4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of liberalization and regionalism upon capital markets in emerging Asian economies

Abstract: This paper examines the trend towards regionalism upon stock market returns for a sample of Asian countries. We find that stock markets are becoming regionally integrated at a faster rate than globally. This finding reflects the growing co-operation between Asian countries. This study focuses upon Indonesia, Malaysia, the Philippines, South Korea, Taiwan and Thailand. These markets suffered severe contagion effects in relation to the Asian financial crisis that occurred during 1997. In addition, this study rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Many countries in Asia region change, especially regarding virtual technology which also expands to the stock markets and it also contributes to the economy. Further, a research conducted by Bilson (2000) also found that the integration of stock markets in Asia region under the study is increasing after the liberalization. Furthermore, financial integration can benefit countries in the region and contribute to the financial development of ASEAn countries whose economics are still far from the developed ones.…”
Section: Literature Review Stock Market Integration In Aseanmentioning
confidence: 73%
See 2 more Smart Citations
“…Many countries in Asia region change, especially regarding virtual technology which also expands to the stock markets and it also contributes to the economy. Further, a research conducted by Bilson (2000) also found that the integration of stock markets in Asia region under the study is increasing after the liberalization. Furthermore, financial integration can benefit countries in the region and contribute to the financial development of ASEAn countries whose economics are still far from the developed ones.…”
Section: Literature Review Stock Market Integration In Aseanmentioning
confidence: 73%
“…the emergence of new technologies and the increasing integration of stock markets around the world lead to the allocation process of stock markets beyond national boundaries (Connoly & Wang 1998). In line with this, Bilson (2000) states that the movement of stock markets in the developing countries and the stock markets in developed countries become more closely related. the forces that drive globalization such as the increasingly rapid global communications, the infrastructure of transportations, and homogenization and the gathering of consumer demands are further enhanced by the reduction of barriers to capital investments in emerging markets.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Oppose to the integrated capital market is segmented capital market. A market is considered as segmented when it has low interrelation with other capital markets (Bilson, 2000;Robiyanto, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…We will also work closely with the ASEAN Capital Market Forum, comprising representatives from ASEAN's securities regulators, to achieve this objective. Bilson, Hooper, and Jaugietis (2000) found that the regional integration among stock markets in Malaysia, the Philippines, South Korea, Taiwan, and Thailand is faster than their integration with the global markets. Sarkar and Li (2002) pointed out that U.S. investors have been slow to acquire foreign stocks, despite economists' claims that diversification is beneficial.…”
mentioning
confidence: 99%